Pengaruh Ekspor Dan Investasi Terhadap Pertumbuhan Ekonomi Di Sumbagsel : Studi Pada Jambi, Bengkulu, Bangka Belitung, Lampung Tahun 2019-2023 - M. Rozak; Rohma Fintia; Eri Widya Mita; Muhammad Kurniawan (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
Economic growth is a reflection of economic development in a country, therefore the government always strives for economic growth to increase every year which will improve people's welfare. The method used is a quantitative method and the type of data used is secondary data obtained from the Ministry of Trade of the Republic of Indonesia and BPS. Meanwhile, the data collection technique is by opening the website of the relevant agency. Data analysis uses multiple linear regression to calculate the magnitude of the influence of exports and investment on South Sumatra's economic growth. Investment has an important role in accelerating the economic development of a country or region, not only encouraging economic growth but also resulting in increasing employment opportunities and reducing investment poverty. It can also be interpreted as an increase in the capital stock used in the production process which results in an increase in the wealth of the country or region. Export activities are a trade activity in which the sale of goods from within the country occurs by complying with applicable regulations. Exports are the total of goods and services sold by another country. This includes goods, insurance and services in a particular year. then net exports in an open economy are a component of aggregate demand buying a portion of domestic output (exports)